The Blessed Virgin Mary As Our Mother. The Lucan Marian Perspective - Kabatha, Zachary Ndegwa (Studia Theologica Varsaviensia, 2019)
The person of the Blessed Virgin Mary among Christians has been throughout Christian tradition a source of inspiration as far as the Christian faith is concerned. Many papal Encyclicals, Apostolic exhortations, conciliar and post conciliar documents have all made reference to our blessed mother due to her close proximity to her son our Lord Jesus Christ. She is thus not a foreigner to the people of faith. The modern man today looks forward for a person who is both faithful and trustworthy to accompany him or her in the earthly life and offer an assurance of everlasting joy. Examining the role of Mary in the writings of St Luke in the New Testament we see Mary as the one who fits in this desire of the modern man. Her role as a mother in the Luke’s view is very central in understanding the notion of companionship. However many people today do not understand Mary to be a faithful companion, perhaps this is due to the misunderstanding of Mary’s position in the Salvation History. Moreover the Sacred Scriptures from the infancy narratives to the neophyte church in Acts of the Apostles Mary makes a journey of faith with Jesus and his disciples. Thus in this article we examine briefly the companionship of the blessed Mary to the Word of God as we invoke her companionship to our Christians today on their pilgrimage to the Promised Land.